Functional and phenotypic analysis of CD4 T cell dynamics in peripheral blood of human visceral leishmaniasis patients confers increased frequencies of CD25 expressing regulatory T cells that contribute to disease pathogenesis - Kamran, Mohd; Ghosh, Smriti; Bhattacharya, Pradyot; Chaudhury, Sneha Ghosh; Bhattacharyya, Anirban; Banik, George; Asad, Mohammad; Ejazi, Sarfaraz Ahmad; Madhukar, Major; Pandey, Krishna; Rahman, Mehebubar; Goswami, Rama Prosad; et al. (Frontiers in Immunology, 2025)
IntroductionRegulatory T cells (Tregs) have been reported to control immune responses in microbial infections. However, their possible role in visceral leishmaniasis (VL) has not been well defined. To address this, we carried out extensive studies to investigate the frequency, phenotype and functions of kala-azar patients’ peripheral blood Tregs pre and post treatment.MethodsFresh blood and peripheral blood mononuclear cells (PBMCs) were used to delineate the frequency and phenotype in VL through flow cytometry. Further for functional characterization, PBMCs of VL patients were depleted of CD25+ T cells and sorted Treg and T effector cells were co-cultured.ResultsTregs frequencies were significantly upregulated in the active VL patients compared to healthy controls and recovered individuals. Tregs characterized as CD4+CD127-/lowCD25high T cells expressed FoxP3 maximally. Isolated Treg cells from VL subjects displayed immunosuppression by inhibiting proliferation and IFN-γ production of effector cells. Moreover, Treg cells were functionally competent and exerted their suppressive role by inhibiting the IFN-γ production and proliferation of effector T cells. Interestingly, when analyzing Treg heterogeneity using the CD45RA marker, we observed an increased frequency of not only effector Treg subpopulations but also naïve and non-Treg cells in active VL patients.ConclusionsThe present study characterizes the frequency, phenotype and function of CD4+CD127-/lowCD25highTreg cells of kala-azar patients ex vivo. Our results suggest that functional effector Treg subpopulation elevated during active VL modulate effectors of immune response and induce immunosuppression. These together with naïve and non-Tregs cells constitute a defining feature of VL pathogenesis.